Correlation of Sonourethrography Findings of Male Anterior Urethral Stricture with Retrograde Urethrography - Gautam, Bishnu; Chataut, Dinesh; Suwal, Sundar; Lohani, Benu (Journal of Institute of Medicine Nepal, 2021)
Introduction Imaging plays significant role in diagnosing the male urethral stricture and helps the urologist in determining the treatment protocols. Retrograde urethrography (RGU) had been the standard imaging technique for anterior urethral stricture. Sonourethrography (SUG) as compared to the retrograde urethrography has the advantage of being radiation free. Aim of this study was to compare the sonourethrography findings in anterior urethral stricture with that of retrograde urethrography. Methods This was an observational study done in 46 patients with clinical symptoms related to lower urinary tract during the period of September 2019 to August 2020 after obtaining informed consent. Ethical clearance was received from Institutional Review committee, Institute of Medicine. Patients were first evaluated by sonourethrography. Then, retrograde urethrography was done as per the standard protocol of the department. Data were collected in the predesignated proforma including the study variables on sonourethrography and retrograde urethrography and entered in IBM SPSS version 20. The lengths of strictures on sonourethrography and retrograde urethrography were compared. Results Among 46 patients 21 patients showed anterior urethral strictures on both SUG and RGU with bulbar region as the commonest location. SUG showed all the urethral strictures seen on RGU with significant positive correlation. SUG also showed spongiofibrosis in nine patients. Conclusion Sonourethrography, an radiation free imaging technique, showed all the strictures seen in retrograde urethrography with added benefit of detection of spongiofibrosis as well.